คุณค่าทางโภชนาการของอาหารที่จัดให้นักเรียนนายร้อยโรงเรียนนายร้อยพระจุลจอมเกล้า(Nutritive Values of Meals Provided for Chulachomklao Royal Military Academy Cadets ) - จินดามณี ภมร (Journal of The Royal Thai Army Nurses, 2012)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อ ประเมินปริมาณพลังงานและสารอาหารจากอาหารที่โรงเลี้ยงโรงเรียนนายร้อยพระจุลจอมเกล้า (รร.จปร.) จัดให้นักเรียนนายร้อย (นนร.) และเปรียบเทียบค่าที่ได้กับ ข้อแนะนำปริมาณอาหารตามธงโภชนาการหรือปริมาณสารอาหารอ้างอิงที่ควรได้รับประจำวันสำหรับคนไทย (Dietary Reference Intake, DRIs) และปริมาณพลังงานและสารอาหารที่ นนร. รับประทานจริงต่อวัน เก็บข้อมูลในภาคการศึกษาที่ 1 ปีการศึกษา 2553 จำนวน 3 มื้อต่อวัน ทั้งหมด 14 วัน ไม่ติดต่อกัน วิเคราะห์ข้อมูลโดยใช้โปรแกรม INMUCAL-Nutrients ของสถาบันโภชนาการ มหาวิทยาลัยมหิดล ใช้สถิติคือค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และร้อยละ ผลการวิจัยพบว่าอาหารที่โรงเลี้ยงจัดให้ นนร. มีปริมาณพลังงานมากกว่า 100 เปอร์เซ็นต์ของข้อแนะนำปริมาณอาหารตามที่ธงโภชนาการกำหนดสำหรับกลุ่มที่ใช้พลังงานมาก ๆ เช่น เกษตรกร ผู้ใช้แรงงาน นักกีฬา เป็นต้น มีการกระจายตัวของพลังงานที่เหมาะสม คือ CHO : Protein : Fat เท่ากับ 60% : 13% : 27% ตามลำดับ มีปริมาณโปรตีน วิตามินบี 1 วิตามินบี 2 และไนอะซิน ธาตุเหล็ก ฟอสฟอรัสมากกว่า 100 เปอร์เซ็นต์ของ DRIs วิตามินเอและวิตามินซีมีปริมาณ 91 เปอร์เซ็นต์ของ DRIs มีปริมาณแคลเซียมและโพแตสเซียม 82 เปอร์เซ็นต์และ 85 เปอร์เซ็นต์ของ DRIs ตามลำดับ มีปริมาณโซเดียมสูงกว่าที่ DRIs กำหนดถึง 5.4 เท่า มีปริมาณคอเลสเตอรอลสูงถึง 2.13 เท่าของค่าที่กรมอนามัยกำหนด และจากการประเมินปริมาณสารอาหารที่ นนร. รับประทานจริงต่อวันพบว่า นนร. ได้รับพลังงาน โปรตีน ธาตุเหล็ก วิตามินบี 1 วิตามินบี 2 เพียงพอกับที่ร่างกายต้องการ แต่การ กระจายตัวของพลังงานยังไม่เหมาะสม สารอาหารกลุ่มวิตามินและแร่ธาตุที่ได้รับไม่เพียงพอ ได้แก่ วิตามินเอ วิตามินซี ไนอะซิน แคลเซียม โพแตสเซียม ได้รับโซเดียมและคอเลสเตอรอลสูงเกินไป ซึ่งจะส่งผลต่อภาวะสุขภาพโดยรวมของ นนร. ได้ คำสำคัญ : คุณค่าทางโภชนาการ, นักเรียนนายร้อย, อาหาร, ปริมาณสารอาหารอ้างอิงที่ควรได้รับประจำวันสำหรับคนไทย Abstract Objectives of this research were to evaluate the nutritive values of meals provided for Chulachomklao Royal Military Academy (CRMA) cadets and to compare the nutritive values of meals with the recommendation of Nutrition Flag or Food Based Dietary Guideline (FBDG) for Thais and Thai DRIs 2003 (Dietary Reference Intake, 2003) and nutritive values of nutrients intake of the study group. The period of data collection was in the first semester of the 2010 academic year. Data were collected form a three meal course each day with the total of 14 days, intermittently. Data were analyzed by the computerized program INMUCAL-Nutrients of the Institute of Nutrition, Mahidol University. Descriptive statistics including means, standard deviations, and percentage were used to evaluate. The results were shown that meals provided for CRMA Cadets has daily energy uptake which was 100% more than that of Nutrition Flag recommendation for people who need such high energy consumption such as farmers, labors, and athletes. The suitable ratio of energy distribution of CHO : Protein : Fat was 60% : 13% : 27%, respectively. With the Thai DRIs 2003 comparison, protein, vitamin B1, vitamin B2, niacin, iron, and phosphorus was 100% more than that of Thai DRIs 2003, vitamin A and vitamin C, however had 91%. Calcium and potassium had 82% and 85%, respectively. Sodium was 5.4 times more than that of Thai DRIs 2003. Cholesterol was 2.13 times higher than the recommendation by the Ministry of Public Health. The evaluation of daily nutrients intake of the study group was found that energy, protein, iron, vitamin B1, and vitamin B2 was sufficient as recommended; nonetheless, the energy distribution was inappropriate. Vitamin A, vitamin C, niacin, calcium and potassium contents were insufficient. Sodium and cholesterol contents were much higher than recommendation. As a results, It will contribute to entire health condition of CRMA Cadets. Keywords: Nutritive Value, Cadets, Meals, DRIs